Analisis Morfologi Redesain Logo “Solo, The Spirit of Java” Terhadap Perkembangan Pariwisata Kota Surakarta (MONTASE : JURNAL DESAIN KOMUNIKASI VISUAL, 2025)
The city of Surakarta, also known as Solo, is a city with a rich cultural and historical heritage. Its tourism potential has led to the city being branded as a center of Javanese culture and traditions. In 2022, the local government changed the city's logo to a new design, which aims to represent Javanese culture and hospitality while also being flexible and dynamic. This research analyzes the new logo from a morphological perspective to determine its effectiveness in communicating the identity of the city. The method used in this research qualitative and descriptive analytics, with data collection through questionnaires from respondents outside the Solo Raya area. The results of the research, including logo morphology analysis and the questionnaire responses, suggest that the new logo is quite effective in attracting tourist interest and communicating the values and characteristics of the region represented by the new logo. Suggestions for future researchers are to study the colour aspect and its impact on influences audience's perception and emotion toward a brand